Tomato-based randomized controlled trial in prostate cancer patients: Effect on PSA. Issue 3 (June 2017) - Paur, Ingvild; Lilleby, Wolfgang; Bøhn, Siv Kjølsrud; Hulander, Erik; Klein, Willibrord; Vlatkovic, Ljiljana; Axcrona, Karol; Bolstad, Nils; Bjøro, Trine; Laake, Petter; Taskén, Kristin A.; Svindland, Aud; et al.
Summary: Background & aims: The effect of lycopene-containing foods in prostate cancer development remains undetermined. We tested whether a lycopene-rich tomato intervention could reduce the levels of prostate specific antigen (PSA) in prostate cancer patients. Methods: Prior to their curative treatment, 79 patients with prostate cancer were randomized to a nutritional intervention with either 1) tomato products containing 30 mg lycopene per day; 2) tomato products plus selenium, omega-3 fatty acids, soy isoflavones, grape/pomegranate juice, and green/black tea (tomato-plus); or 3) control diet for 3 weeks. Results: The main analysis, which included patients in all risk categories, did not reveal differences in changes of PSA-values between the intervention and control groups. Post-hoc, exploratory analyses within intermediate risk (n = 41) patients based on tumor classification and Gleason score post-surgery, revealed that median PSA decreased significantly in the tomato group as compared to controls (−2.9% and +6.5% respectively, p = 0.016). In separate post-hoc analyses, we observed that median PSA-values decreased by 1% in patients with the highest increases in plasma lycopene, selenium and C20:5 n-3 fatty acid, compared to an 8.5% increase in the patients with the lowest increase in lycopene, selenium and C20:5 n-3 fatty acid (p = 0.003). Also, PSA decreased in patients with the highest increase in lycopene alone (p = 0.009). Conclusions: Three week nutritional interventions with tomato-products alone or in combination with selenium and n-3 fatty acids lower PSA in patients with non-metastatic prostate cancer. Our observation suggests that the effect may depend on both aggressiveness of the disease and the blood levels of lycopene, selenium and omega-3 fatty acids.